Discourse structuring markers in English a historical constructionalist perspective on pragmatics - Traugott, Elizabeth Closs (Constructional Approaches to Language Ser., 2022)
"This book is a contribution to the growing field of diachronic construction grammar. Focus is on corpus evidence for the importance of including conventionalized pragmatics within construction grammar and suggestions for how to do so. The empirical domain is the development of Discourse Structuring Markers in English such as after all, also, all the same, by the way, further and moreover (also known as Discourse Markers). The term Discourse Structuring Markers highlights their use not only to connect discourse segments but also to shape discourse coherence and understanding. Monofunctional Discourse Structuring Markers like further, instead, moreover are distinguished from multifunctional ones like after all and by the way. Drawing on usage-based work on constructionalization and constructional changes, the book is in three parts: foundational concepts, case studies, and currently open issues in diachronic construction grammar. These open issues are how to incorporate the concepts subjectification and intersubjectification into a constructional account of change, whether position in a clause is a construction, and the nature of constructional networks and how they change"--